Structural And Functional Understanding Of Srotas In Rachana Sharir With Special Reference To Moola Sthana - Dr. Sumedha; Dr. Lal Kaushal (Journal for ReAttach Therapy and Developmental Diversities, 2022)
Background: Srotas are integral anatomical and functional pathways described in Ayurveda, facilitating the transportation of Rasa, Rakta, and other Dhatus and Malas. In Rachana Sharir, they represent a structured network of channels with defined origins (Moola Sthana) responsible for initiating and regulating specific physiological functions. The Moola Sthana concept, as explained in Charaka Samhita and Sushruta Samhita, identifies primary anatomical sites that control and maintain the patency of each Srotas. A systematic study of their structure and function helps bridge classical Ayurvedic knowledge with modern anatomical understanding, enhancing diagnostic and therapeutic approaches. Aim: To study the structural and functional aspects of Srotas in Rachana Sharir with special reference to their Moola Sthana. Objectives: To review classical descriptions of Srotas and their Moola Sthana. To correlate Moola Sthana with modern anatomical structures. To assess the functional significance of Moola Sthana in health and disease. Materials and Methods: A literary review was conducted using primary Ayurvedic texts (Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya) along with classical commentaries. Modern anatomical references were consulted to establish correlations. Data extraction involved identification of each Srotas, its Moola Sthana, structural description, and functional attributes. Comparative tables and diagrams were used for analysis. Results: Classical sources describe 13 pairs of Srotas, each with specific Moola Sthana, structural composition (Mamsa, Sira, Snayu, Asthi, Sandhi), and functional attributes. Correlation with modern anatomy suggests similarities with vascular, lymphatic, respiratory, gastrointestinal, and genitourinary systems. Moola Sthana acts as the primary anatomical and physiological control point, with dysfunctions leading to specific Srotodushti Lakshana. Conclusion: Understanding the Srotas and their Moola Sthana from both Ayurvedic and modern anatomical perspectives enhances the comprehension of physiological processes, early disease identification, and targeted therapeutic interventions. This integrated view supports the relevance of Rachana Sharir in contemporary health sciences.